Pengukuran Kinerja dan Keamanan Server di RSUD Koja - Alita Sandy Putriani; Arief Ichwani; Hosizah Hosizah; Imam Sutanto (Jurnal Informatika Dan Tekonologi Komputer (JITEK), 2026)
The rapid development of health services currently requires every health service provider to be able to immediately meet the desires of its customers. The use of information technology requires a comprehensive security system. One of these security is physical security. In addition to physical security, the need to store and use data quickly needs to be a must for organizations. This type of research is qualitative research with a case study approach. The results of this study, to measure server performance using the JMeter tool. Testing was carried out on the web from the Nutanix server with 3 tests. So there is a difference in the number of requests where in test 3 the number of requests increased much more with a lower number of samples than the number of requests and the number of samples from the previous 2 tests. While to measure server security using OWAS ZAP with very good results, there is only 1 with a high risk level, namely a vulnerability with a high impact.